4f=3+f

Simple and best practice solution for 4f=3+f equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4f=3+f equation:


Simplifying
4f = 3 + f

Solving
4f = 3 + f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-1f' to each side of the equation.
4f + -1f = 3 + f + -1f

Combine like terms: 4f + -1f = 3f
3f = 3 + f + -1f

Combine like terms: f + -1f = 0
3f = 3 + 0
3f = 3

Divide each side by '3'.
f = 1

Simplifying
f = 1

See similar equations:

| v=4/3X3.14X10X2 | | -9s+8=-10s | | 4x-3x+7=12x-6-9 | | 1/6c=12 | | 4x+4=5x+6 | | x^2-4x+4=10 | | 7m^3-80m^2+100m=0 | | -4+3j=2j | | 15+0.17x=40 | | 35=2y+9 | | 21xy-7x= | | -9/10b=-18 | | x+250y=1000 | | y+6.2=-2.4 | | (2x-6)(x-1)=0 | | (-10-5x)-1=14 | | -(4a-3b+5c)= | | x=b-8/a-1 | | factorx^2+10x-24=0 | | 7k+3=5 | | Y=9-2x+3 | | 5=-16x^2+45x+6 | | Y=5x^2-7x-6 | | 7w-5=-4(w-7) | | 12a-9=3 | | ln(x)-ln(5)=5 | | -32=-8u | | log(4x+24)=3 | | 5=16/x | | (3x+14)=(7x) | | 63=25x | | -28x^2-32x+16=0 |

Equations solver categories